Pediatric Sepsis: Genetic Considerations - Elek, N.; Sandor, S.; Balazs, G.; Dahlem, P. (Journal of Child Science, 2017)
The mortality of childhood sepsis continues to be rather high. When it comes to prevention and adequate therapy, individual differences and genetic alterations are becoming more and more important. These may affect molecules involved in pathogen recognition (e.g., lipopolysaccharide-binding protein, mannose-binding lectin, bactericidal/permeability-increasing protein, Toll-like receptors), signal transduction pathways (e.g., cRel), proinflammatory (e.g., tumor necrosis factor-α, interleukin-1 [IL-1], IL-6, IL-8) as well as anti-inflammatory cytokines (e.g., IL-4, IL-10, IL-1 receptor antagonist), members of the coagulation cascade, and other molecules active in the process of systemic inflammatory response syndrome (e.g., heat shock proteins, complement system). The most common genetic polymorphisms are the so-called single-nucleotide polymorphisms, which entail the change of a single base. Genetic mutations have an impact on susceptibility, severity, and outcome of sepsis. Understanding such mutations may improve treatment efficiency; although there is a considerably limited choice of causal treatments today, they may become available upon future developments in genetic therapy.
Keywords: sepsis; infection; genetics; childhood; polymorphism; single-nucleotide polymorphism; review; systemic inflammatory response syndrome